Karakterisasi Dan Potensi Penyisihan Pada Pome Menggunakan Proses Ozonasi - Shifa Rayni Efendi; David Andrio; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
POME has high pollutants. POME is thick brown. The color of POME is associated with complex compounds derived from polymerization between the degraded products lignin and tannins, and POME has a high chemical composition and concentration of simple organic compounds. POME is a major source of water pollution because it is difficult to decompose and is dangerous for the environment. This research aims to investigate the characteristics of POME by analysis using ozonation. The results showed an decrease in COD from 58.144 mg/L to 56.181 mg/L. Keywords: POME, ozonation